Supplementation with Zn-loaded montmorillonite enhanced Zn ion transport, trace element deposition, antioxidant capacity, and intestinal function in broilers - Shizhen Qin; Haibo Wang; Shijiao Qin; Jinlv Li; Defu Tang; Zhaoguo Shi (Frontiers in Veterinary Science)
This study aimed to investigate the effects of dietary zinc-loaded montmorillonite (Zn-MMT) on performance, Zn transporter expression, metal deposition, antioxidant capacity, and intestinal function in broilers. A total of 144 one-day-old male Cobb broilers were randomly divided into three treatment groups. The broilers in the control group (CK) were fed a corn–soybean meal basal diet, while the experimental groups were fed a basal diet supplemented with 40 mg/kg Zn-MMT and ZnSO4 (in terms of Zn content). The results showed that Zn-MMT had no significant (p > 0.05) effect on average daily gain (ADG), average daily feed intake (ADFI), or carcass parameters, but it significantly (p < 0.05) reduced the feed-to-gain (F: G) ratio. Dietary Zn supplementation increased (p < 0.05) the expression of Zn transporter 1 (ZnT-1), Zn transporter 5 (ZnT-5), metallothionein (MT), and MTF-1 mRNA in the jejunum and the Zn content in the tibia and whole blood. In addition, it increased (p < 0.05) total antioxidant capacity (T-AOC) and Cu/Zn-SOD while reducing (p < 0.05) malondialdehyde (MDA) levels in the liver and jejunum. However, no significant effect (p > 0.05) was observed on the microbial population in the cecum. Furthermore, compared to the CK and ZnSO4 groups, Zn-MMT significantly (p < 0.05) increased the mRNA expression of MT-3 and divalent metal transporter 1 (DMT-1) in the jejunum and promoted the storage of Zn in the liver and pancreas. It also significantly (p < 0.05) increased villus height (VH) and the villus heightto-crypt depth (VH/CD) ratio in the duodenum and jejunum, increased the VH/CD ratio in the ileum, and reduced CD in the duodenum. In conclusion, supplementation with Zn-MMT in a corn–soybean meal basal diet can increase the expression of metal transporters, promote Zn deposition, enhance antioxidant capacity, improve intestinal tissue parameters, and increase Zn utilization.